ANALISIS PELUANG DAN TANTANGAN PERDAGANGAN PRODUK TEKSTIL ANTARA INDONESIA DENGAN KOREA SELATAN (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the development of textile exports in Indonesia to South Korea and also identify international trade opportunities and challenges that arise in. At the beginning of the implementation of the IK-CEPA on January 1, 2023, the value of Indonesian textile exports to South Korea increased significantly. But on the other hand, the textile industry in Indonesia still faces serious challenges such as intense competition from other foreign countries, the quality of products that need to be considered, and the costs of the production process.